ANALISIS KEPUTUSAN ETIS DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI BENGKULU - Yusuarsono - (Professional: Jurnal Komunikasi dan Administrasi Publik, 2015)
This study aimed to determine the Empl oyee Ethical Decision Legislative Council  Secretariat Bengkulu province. The research  method was qualitative. Informants in this  study were all secretariat employees of th e Regional Representatives Council of Bengkulu p rovince. Data was collected by using pur posive sampling technique through interviews.  Data analysis was performed through three (3) st ages: reduction, display, and inference and  verification. The results showed that ethi cal decision on the Secretariat of Bengkulu  Province Council seen from benefits criteria,  some decisions are tied to the interest of  Council’s member. Seen from rights criteria, the Council membe rs didn’t focus on the rights  and interests of all organization or instances  and employees. If it’s seen from fairness  criteria, the fairness doesn’t applied well for the lazy and  diligent employees receive the  same honorarium. In addition the appointment of  PPTK (Official Technical Users Activity)  only employees who are close to the leaders  who were appointed. However, because it’s the  leader’s decision, all employees must comply. Li kewise with seniority, works often given to  senior employees without involving the new on es, so that the new employees are learning  slowlyKeywords: Ethical Decision Criteria Benefits, Council, Employee